Design and realization of the real-time monitoring system for instant messenger - FU An-min1; ZHANG Yu-qing2 (Tongxin xuebao)
On the base of the deep study and analysis of the various instant messengers’ transmission protocol of texts,files,audios and videos,A real-time monitoring system for instant messenger——IMmonitor was designed and realized.The system can not only real-timely monitor the text message of the instant messengers（such as MSN,Fetion,ICQ etc.） for multiple versions,but also monitor the transmission of any files（such as.doc,.jpg,.rar etc.）,audios and videos.The IMmonitor system has realized the comprehensive monitor of the all formats of information of the instant messengers,and has solved the problem of the upgrade of the monitor system,which is caused by the upgrade of the instant messenger.